Saudi Society of Diabetes Position Statement on Herpes Zoster Vaccination in Adults with Diabetes - Abdulrahman Alshaikh; Nasser Aljuhani; Fahad Alsabaan; Amani Alhozali; Lamya Alzubaidi; Ali Alshehri; Emad R Issak; Hussein Elbadawi; Ali Albarrak; Mahmoud Amer; Saud Alsifri (Saudi Journal of Medicine, 2026)
Background: Adults with diabetes mellitus (DM) are at increased risk of herpes zoster (HZ) and its complications because of impaired cell-mediated immunity, chronic hyperglycemia, and multiple comorbidities. Despite the availability of highly effective recombinant zoster vaccine (RZV), vaccine uptake remains suboptimal among patients with diabetes in Saudi Arabia. This consensus statement was developed to provide evidence-based recommendations for HZ vaccination in adults with DM within the Saudi healthcare setting. Methods: A multidisciplinary expert panel convened under the auspices of the Saudi Society of Diabetes conducted structured evidence review and consensus process. A comprehensive literature search of PubMed/MEDLINE, Embase, Scopus, Web of Science, and the Cochrane Library was performed to identify studies published during the previous 10 years on HZ epidemiology, vaccine efficacy and safety, and vaccination strategies in adults with diabetes. Evidence was critically appraised and integrated with expert opinion using a modified Delphi-informed consensus approach. Recommendations were categorized according to evidence strength (Level A–C) and aligned with national immunization policies. Results: Available evidence consistently demonstrates that diabetes is associated with an increased risk of HZ, postherpetic neuralgia, hospitalization, and other complications. Saudi epidemiological data identified 1,019 HZ cases over a 6-year period, with 31.3% developing complications, 12.5% requiring hospitalization, and 1.2% requiring intensive care. Randomized trials and real-world studies demonstrate that RZV provides approximately 94% efficacy against HZ with durable protection and an acceptable safety profile. The expert panel developed 10 evidence-based recommendations addressing patient selection, vaccination timing, immunocompromised populations, co-administration with other vaccines, risk stratification, healthcare provider education, patient awareness, electronic reminder systems, equitable vaccine access, and pharmacovigilance. The panel emphasized routine assessment of vaccination status during diabetes care and strong physician recommendation as key strategies to improve vaccine uptake. Conclusion: Adults with diabetes represent a high-risk population for herpes zoster and should be prioritized for recombinant zoster vaccination according to current national recommendations. Integrating vaccination assessment into routine diabetes care, strengthening healthcare provider engagement, and implementing system-level interventions may substantially improve vaccination coverage and reduce the burden of HZ among adults with diabetes in Saudi Arabia.